Preventing Infections by Encapsulated Bacteria Through Vaccine Prophylaxis in Inflammatory Bowel Disease - Lenti, Marco Vincenzo; Mengoli, Caterina; Vernero, Marta; Aronico, Nicola; Conti, Laura; Borrelli de Andreis, Federica; Cococcia, Sara; Di Sabatino, Antonio (Frontiers in Immunology, 2020)
Inflammatory bowel disease (IBD), which comprises ulcerative colitis and Crohn’s disease, is an immune-mediated, chronic-relapsing, disabling disorder which is associated with increased mortality and poor patients’ quality of life. Patients with IBD are at increased risk of infections for many reasons. In fact, IBD often requires a lifelong immunosuppressive and/or biologic therapy, both commonly associated with respiratory and opportunistic infections, but also gastrointestinal, urinary tract infections, and sepsis. Moreover, impaired spleen function has been found in a considerable proportion of IBD patients, further increasing the risk of developing infections sustained by encapsulated bacteria, such as S. pneumoniae, H. influenzae, and N. meningitidis. Finally, comorbidities and surgery represent additional risk factors for these patients. Despite the availability of vaccinations against the most common serotypes of encapsulated bacteria, uncertainties still exist regarding a proper vaccination strategy and the actual effectiveness of vaccinations in this particular setting. Aim of this narrative review is to focus on the broad topic of vaccinations against encapsulated bacteria in IBD patients, discussing the clinical impact of infections, predisposing factors, vaccinations strategies, and unmet research and clinical needs.